Relevansi Kiprah Nabi Amos Amos. 2:6-8 Bagi Perjuangan Truk F di Kabupaten Sika - Jehampu, Rikardus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
In simple terms, justice means giving someone what is right. Justice is still a utopian hope. This is because there are many cases of injustice that still often occur today, both in the political, religious and customary shutters. The current rise of injustice cases encourages us to dare to fight for justice and defend the rights of its victims. The prophet Amos in the Old Testament is one of the only figures who fought for justice in the midst of the situation of the Israelites who were full of injustice. This is seen in Am 8:4-6 which contains a complaint for those who commit acts of injustice against the poor and weak. In this day and age, injustice has become a universal disease. Injustice occurs everywhere, including in Sikka Regency. Many cases of injustice that occur in Sikka Regency, even from some cases no longer feel strange to the ears and eyes of the community. This phenomenon of injustice is often experienced by the poor and the weak. Just to mention several cases of injustice in Sikka Regency, such as human trafficking, harassment of women and weak law enforcement agencies. Facing this reality, the people of Sikka Regency need a driving figure who voices justice like the prophet Amos. Therefore, the group sees that the driving figure to fight for justice is present in the Women's Division of TRUK F. TRUK F is a non-governmental organization engaged in the humanitarian field. Like the prophet Amos who called for justice, TRUK F is also present as an instrument to voice justice in Sikka Regency. Therefore, the title of the article that we presented is the Relevance of the Work of the Prophet Amos for the Struggle of TRUK F in Sikka Regency.